Experimental Study on the Coupling Dynamics of Metal Jet, Waves, and Bubble During Underwater Explosion of a Shaped Charge - Yu Tian; A-Man Zhang; Liu-Yi Xu; Fu-Ren Ming (Engineering, 2025)
Unlike conventional spherical charges, a shaped charge generates not only a strong shock wave and a pulsating bubble, but also a high strain rate metal jet and a ballistic wave during the underwater explosion. They show significant characteristic differences and couple each other. This paper designs and conducts experiments with shaped charges to analyze the complicated process. The effects of liner angle and weight of shaped charge on the characteristics of metal jets, waves, and bubbles are discussed. It is found that in underwater explosions, the shaped charge generates the metal jet accompanied by the ballistic wave. Then, the shock wave propagates and superimposes with the ballistic wave, and the generated bubble pulsates periodically. It is revealed that the maximum head velocity of the metal jet versus the liner angle α and length-to-diameter ratio λ of the shaped charge follows the laws of 1/(α/180°)0.55 and λ0.16, respectively. The head shape and velocity of the metal jet determine the curvature and propagation speed of the initial ballistic wave, thus impacting the superposition time and region with the shock wave. Our findings also reveal that the metal jet carries away some explosion products, which hinders the bubble development, causing an inward depression of the bubble wall near the metal jet. Therefore, the maximum bubble radius and pulsation period are 5.2% and 3.9% smaller than the spherical charge with the same weight. In addition, the uneven axial energy distribution of the shaped charge leads to an oblique bubble jet formation.